2000
DOI: 10.1021/ma9919514
|View full text |Cite
|
Sign up to set email alerts
|

Surface Dynamics in Rubbed Polymer Thin Films Probed with Optical Birefringence Measurements

Abstract: Measurements of the optical birefringence were used to probe the relaxation of rubbed ultrathin polystyrene (PS) films on glass substrates. It was found that the glass transition temperature, T g, of the films dropped by 15-20 K as the film thickness decreased from 10 µm to 5.8 nm. Experiments on thick films (∼10 µm) revealed that molecules closer to the polymer-air interface relax more quickly than molecules farther from the interface. These results are explained in the context of past experimental studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
87
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 34 publications
(139 reference statements)
12
87
2
Order By: Relevance
“…9 In particular, good quantitative agreement between the change in T g 19 and the change in T 0 as the PS film thickness is decreased from 50 to 10 nm supports the viewpoint that T 0 is directly related to T g . 8,9 This result, consistent with the previous finding that T 0 has the same M w dependence as T g , 12 suggests that the ␣ relaxation may dominate the observed relaxations of the rubbed PS films near T g . Moreover, at thicknesses greater than 30 nm, the T 0 's of PS films on HOSi are lower than those on SiO 2 surfaces.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…9 In particular, good quantitative agreement between the change in T g 19 and the change in T 0 as the PS film thickness is decreased from 50 to 10 nm supports the viewpoint that T 0 is directly related to T g . 8,9 This result, consistent with the previous finding that T 0 has the same M w dependence as T g , 12 suggests that the ␣ relaxation may dominate the observed relaxations of the rubbed PS films near T g . Moreover, at thicknesses greater than 30 nm, the T 0 's of PS films on HOSi are lower than those on SiO 2 surfaces.…”
Section: Resultsmentioning
confidence: 62%
“…Similar behavior has been observed before. 8,9 For PS films on SiO 2 , T 0 becomes smaller for thinner films. For PS films on HOSi, however, T 0 remains the same for all thicknesses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With all the above observations, it is puzzling that hours of annealing at temperature much higher than the T g is needed for PMMA surface to equilibrate, as it is expected that molecules on the surface relax much faster than the ones in the bulk. 25 In addition, there are limited surface studies of PMMA as a function of tacticity, in spite of the impact tacticity may have on the surface properties. 26 Recent SFG study from Tanaka et al 7 concluded that syndiotactic PMMA (syn-PMMA) had both backbone methylene and estermethyl groups ordered at the surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…24 The mechanical rubbing of polystyrene (PS) surfaces can also produce homogeneous planar LC alignment layers, where the LC molecules are aligned perpendicular to the rubbing direction. [25][26][27][28][29][30][31][32][33] However, this perpendicular LC alignment produces a very low pretilt angle of about 0 o26,31 as well as a weak azimuthal anchoring energy of less than 10 -7 -10 -8 J/m 2 , 31-33 which is too low to produce a stable LC cell for practical applications in LCD devices. The homogeneity of an LC cell fabricated with the rubbed PS film is lost after 1 day.…”
Section: Introductionmentioning
confidence: 99%